Biological Markers of Suicidal Behavior in Patients with Severe Mental Illness: A Narrative Review - Cárdenas Urbano, Rafael Santiago; Vera Henao, Sebastián; García Valencia, Jenny; López Jaramillo, Carlos (Iatreia)
Introduction: Suicide is a significant public health concern, and mental illnesses are among the prominent risk factors. In the pursuit of early detection of suicidal behaviors, various predictive markers have been studied in psychiatric populations. Objectives: To present a narrative review of biological markers associated with suicide. Methodology: A literature search was conducted using PubMed, SCIELO, Science Direct, and EMBASE databases. The search terms included ‘severe mental illness’, ‘bipolar affective disorder’, ‘major depression’, ‘schizophrenia’, ‘suicide’, and ‘markers’. Studies in both Spanish and English were considered, and articles available up to August 2023 were included, regardless of study design. Articles related to other mental illnesses were excluded. Results: The biological markers most extensively studied in relation to suicidal behaviors in severe mental illness are monoamine systems and systemic inflammatory molecules. Genetic markers, particularly those associated with serotonin and the hypothalamic-pituitary-adrenal (HPA) axis, have also gained significance in recent years. Conclusions: There has been notable research on biological markers in relation to suicidal behavior in populations with severe mental illness. However, further investigation into other pathophysiological mechanisms of suicide is needed.